Generalized Rational Evaluation Subgroups of the Inclusion between Complex Projective Spaces - Gatsinzi, Jean-Baptiste (Armenian Journal of Mathematics, 2023)
We use a model of mapping spaces to compute the generalized rational Gottlieb groups of the inclusion $i_{n,k}: \mathbb{C}P^n \hookrightarrow \mathbb{C}P^{n+k}$ between complex projective spaces.